The influence of emulsion structure on the Maillard reaction of ghee. (15th April 2015) - Newton, Angela E.; Fairbanks, Antony J.; Golding, Matt; Andrewes, Paul; Gerrard, Juliet A.
Highlights: Inverse emulsions were formed to study the effect of structure on the Maillard reaction. SPME GCMS analysis of changes in the formation of volatile compounds during cooking. The generation of different volatile compound profiles through the use of inverse emulsion structures. Monitoring of changes in emulsion structure during high temperature cooking using light microscopy. Abstract: Food systems, such as cream and butter, have an emulsion or emulsion-like structure. When these food emulsions are heated to high temperatures to make products such as ghee, the Maillard reaction forms a range of volatile flavour compounds. The objective of this paper was to unravel the specific influence of emulsion structure on the Maillard reaction pathways that occur during the cooking of ghee using model systems. Switching the dispersed phase from oil to water provided a means of altering the ratios of volatile compounds produced in the cooked samples. The oil-in-water emulsion generated a volatile compound profile similar to that of the fat containing two phase model matrix, whereas the water-in-oil emulsion produced a different ratio of these compounds. The ability to generate different volatile compound profiles through the use of inverted emulsion structures could point to a new avenue for control of the Maillard reaction in high temperature food systems.